Physiological response of gmelina (gmelina arborea roxb.) to hydric conditions of the colombian caribbean (2012)
Gmelina is an important forest species because of its adaptability to different tropical environments, rapid growth and high quality wood for many uses. Although the species thrives in lowlands, both wet and dry, water availability is the main limiting factor for production in the latter. The transpiration rate, stomatal resistance, water potential and chlorophyll and carotenoid pigments content were monitored for three climatic seasons (rainy, transitional and dry) and three ages (seedling (2-10 months), juvenile (10-16 months) and adult (48-60 months)), in order to observe the physiological response of gmelina to conditions in northern Colombia. Transpiration rates decreased with the age of the trees and the critical value of leaf water potential, that generates stomatal closure, was observed below -2.6 MPa. The dry season resulted in increased carotenoid content, in contrast to the content of chlorophyll A, B and total.